ChemInform Abstract: Enantioselective Fluorination of β‐Ketoesters Catalyzed by Complexes of New Mono‐Oxazoline Ligands. Issue 40 (October 2015) - Niu, Teng; Han, Xiping; Huang, Danfeng; Wang, Ke‐Hu; Su, Yingpeng; Hu, Yulai; Fu, Ying
Abstract A new kind of mono‐oxazoline ligand (OXP) is prepared and used as catalyst for the enantioselective fluorination of β‐ketoesters by NFSI.